Characterization and Otoprotective Effects of Polysaccharides from Arthrospira platensis - Matteo Banti; Mercedes Garcia-Gil; Lorenzo Guidotti; Graziano Di Giuseppe; Simona Rapposelli; Daniela Monti; Silvia Tampucci; Marinella De Leo; Francesca Gado; Paola Nieri; Clementina Manera (Molecules)
Hearing loss is one of the most common sensory disorders in humans, and a large number of cases are due to ear cell damage caused by ototoxic drugs including anticancer agents, such as cisplatin. The recent literature reported that hearing loss is promoted by an excessive generation of reactive oxygen species (ROS) in cochlea cells, which causes oxidative stress. Recently, polysaccharides from the cyanobacterium Arthrospira platensis showed many biological activities, including antioxidant activity, suggesting their potential use to combat hearing loss. On these bases, this study describes the extraction, purification, and characterization of water-soluble polysaccharides from A. platensis (SPPs) and the investigation of their protective role against cisplatin toxicity on House Ear Institute-Organ of Corti (HEI-OC1) cells. The results showed that SPPs (5–80 µg/mL) induced a dose-dependent increase in viability, statistically significant at 40 µg/mL and 80 µg/mL. Moreover, SPPs, evaluated at 80 µg/mL, inhibited the cisplatin-induced ROS level increase in HEI-OC1. This evidence highlights the potential of SPPs as natural candidates to protect cochlear ear cells against ototoxic oxidative agents. Moreover, in view of the potential use of microalgal polysaccharides to realize hydrogels, SPPs could also represent a healthy carrier for other topically administered otoprotective agents.